Preparation and Characterization of Cyperus-Derived Exosomes Loaded with Selenium Nanoparticles for Selenium Delivery Based on Exosome Protein Quantitation - Dexiu Zhao; Xiaojun Yang; Abulimiti Kelimu; Bin Wu; Weicheng Hu; Hongbo Fan; Lei Jing; Dongmei Yang; Xinhong Huang (Foods)
Appropriate carriers or templates are crucial for maintaining the stability, biological activity, and bioavailability of selenium nanoparticles (SeNPs). Selecting suitable templates remains challenging for fully utilizing SeNPs functionalities and developing applicable products. Exosome-like nanoparticles (ELNs) have gained importance in drug delivery systems, yet research on selenium products prepared using exosomes remains limited. To address this gap, we utilized Cyperus bean ELNs to deliver SeNPs, investigated three preparation methods for SeNPs-ELNs, identified the optimal approach, and performed characterization studies. Notably, all three methods successfully loaded SeNPs. Ultrasonic cell fragmentation is the optimal approach, achieving significant increases in selenium loading (5.59 ± 0.167 ng/μg), enlargement of particle size (431.17 ± 10.78 nm), and reduced absolute zeta potential (−4.1 ± 0.43 mV). Moreover, both exosome formulations demonstrated enhanced stability against aggregation during storage at 4 °C, while their stability varied with pH conditions. In vitro digestibility tests showed greater stability of SeNP-ELNs in digestive fluids compared to ELNs alone. Additionally, neither ELNs nor SeNP-ELNs exhibited cytotoxicity toward LO2 cells, and the relative erythrocyte hemolysis remained below 5% at protein concentrations of 2.5, 7.5, 15, 30, and 60 μg/mL. Overall, ultrasonic cell fragmentation effectively loaded plant-derived exosomes with nano-selenium at high capacity, presenting new opportunities for their use as functional components in food and pharmaceutical applications.